Cryosectioning. Issue 1 (17th January 2022) - Ross, Mark A.; Kohut, Lauryn; Loughran, Patricia A.
Abstract: The protocols presented here describe steps for cryosectioning tissue samples to be used in light microscopy methodologies including histochemistry, enzyme immunohistochemistry, and immunofluorescence. © 2022 Wiley Periodicals LLC. Basic Protocol 1 : Cryosectioning